2012
DOI: 10.4049/jimmunol.1201538
|View full text |Cite
|
Sign up to set email alerts
|

Abelson Tyrosine Kinase Controls Phagosomal Acidification Required for Killing of Mycobacterium tuberculosis in Human Macrophages

Abstract: The mechanisms that regulate the acidification of intracellular compartments are key to host defense against pathogens. In this paper, we demonstrate that Abl tyrosine kinase, a master switch for cell growth and trafficking of intracellular organelles, controls the acidification of lysosomes in human macrophages. Pharmacological inhibition by imatinib and gene silencing of Abelson (Abl) tyrosine kinase reduced the lysosomal pH in human macrophages by increasing the transcription and expression of the proton pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 60 publications
11
100
0
Order By: Relevance
“…Several protein kinase inhibitors are available for clinical use. 129 Imatinib, a tyrosine kinase inhibitor, reduces bacterial load and lung pathology, likely by enhancing autophagy, phagosomal acidification and myeloid cell mobilization, [130][131] and is currently being tested for its safety and immunogenicity as repurposed TB treatment. Adenosine monophosphate-activated protein kinase (AMPK) regulates cellular energy levels, T-cell differentiation and development of memory.…”
Section: Kinase Modulatorsmentioning
confidence: 99%
“…Several protein kinase inhibitors are available for clinical use. 129 Imatinib, a tyrosine kinase inhibitor, reduces bacterial load and lung pathology, likely by enhancing autophagy, phagosomal acidification and myeloid cell mobilization, [130][131] and is currently being tested for its safety and immunogenicity as repurposed TB treatment. Adenosine monophosphate-activated protein kinase (AMPK) regulates cellular energy levels, T-cell differentiation and development of memory.…”
Section: Kinase Modulatorsmentioning
confidence: 99%
“…Subsequent reports showed that Abl kinases are also required for infection by several bacteria (e.g. Helicobacter pylori, EPEC, Salmonella enterica, Anaplasma phagocytophilum, Pseudomonas aeruginosa, Chlamydia trachomatis, Mycobacterium tuberculosis) (Bauer et al, 2009;Bruns et al, 2012;Elwell et al, 2008;Jayaswal et al, 2010;Lin et al, 2007;Ly and Casanova, 2009;Muller, 2012;Napier et al, 2011;Pielage et al, 2008;Poppe et al, 2007;Swimm et al, 2004;Tammer et al, 2007) and viruses [vaccinia virus,coxsackievirus,enterovirus 71 (EV71), HIV, hepatitis C virus (HCV) and Ebola virus] (Chen et al, 2007;Coyne and Bergelson, 2006;Garcia et al, 2012;Harmon et al, 2010;Newsome et al, 2006;Reeves et al, 2005;Yamauchi et al, 2015). Microbial pathogens exploit the ability of Abl kinases to regulate cytoskeletal processes in order to achieve efficient internalization, intracellular motility, pedestal formation, cell-to-cell spread, membrane modeling and release (egress).…”
Section: Box 2 Microbial Pathogens Subvert the Function Of Abl Kinasmentioning
confidence: 99%
“…Mtb is a highly successful pathogen that is able to manipulate and prevent phagosome acidification and maturation of this compartment [43]. This phenomenon was recently demonstrated to be controlled by Abl tyrosine kinases and could be reversed by the Abl tyrosine kinase inhibitor imatinib [44]. Mtb can also impair phagolysosomal fusion.…”
Section: Phagolysosome and Autophagymentioning
confidence: 99%